2018
DOI: 10.1016/bs.aambs.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-Function Relationships in Natural, Applied, and Engineered Microbial Ecosystems

Abstract: The connection between ecosystem function and taxonomic diversity has been of interest and relevance to macroecologists for decades. After many years of lagging behind due to the difficulty of assigning both taxonomy and function to poorly-distinguishable microscopic cells, microbial ecology now has access to a suite of powerful molecular tools which allow its practitioners to generate data relating to diversity and function of a microbial community on an unprecedented scale. Instead, the problem facing today'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 245 publications
(280 reference statements)
1
7
0
Order By: Relevance
“…Firstly, the SHC group cows exhibited a noticeably higher community diversity (α and β diversity) within their intestinal microbiota was detected. This observation supports the notion that increased diversity within an ecosystem can improve its stability, productivity, and overall functioning ( Free et al, 2018 ). Furthermore, studies have revealed a correlation between a higher growth rate and enhanced diversity in the intestinal microbial community of human infants ( Ford et al, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…Firstly, the SHC group cows exhibited a noticeably higher community diversity (α and β diversity) within their intestinal microbiota was detected. This observation supports the notion that increased diversity within an ecosystem can improve its stability, productivity, and overall functioning ( Free et al, 2018 ). Furthermore, studies have revealed a correlation between a higher growth rate and enhanced diversity in the intestinal microbial community of human infants ( Ford et al, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…α‐diversity metrics are used to estimate biodiversity of the microbial community. Ecologically, α‐diversity is proposed to correlate with the health of an ecosystem, as diverse communities may increase the stability and productivity of an ecosystem (28). In the present study, the analysis of α‐diversity did not show any significant differences between the ND‐LL and ND‐LD groups.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, while biostimulation can be very effective in increasing the rate of hydrocarbon degradation, bioaugmentation can have a limited long-term effect (Fuentes et al, 2016;Galitskaya et al, 2016;Wozniak-Karczewska et al, 2019). The latter is a general phenomenon also associated with bioremediation of other toxic compounds such as organohalides (Beaudet et al, 1998), and may be because it is difficult for an exogenous species to become stably established in a competitive community environment (Free et al, 2018). In addition, delivery of microbial inocula to contaminated environments, such as soil, in situ is potentially problematic.…”
Section: Introductionmentioning
confidence: 99%